Teaching with Spiritual Impact: An Analysis of Student Comments Regarding High‐ and Low‐Rated Spiritually Inspiring Religion Classes. (October 2016) - Hilton, John; Sweat, Anthony; Griffin, Tyler; Griffiths, Casey Paul
Abstract: We analyzed 2, 621 written student comments to better understand themes which most contribute to religion classes being rated high or low in terms of the spiritual benefit students received from the class. From 2, 448 religion classes taught from September of 2010 through April of 2014, comments from the top 61 (2.5 percent) and bottom 51 (2.1 percent) rated classes in terms of being "spiritually inspiring" were compared for emerging themes. The most frequent themes in higher‐ranked spiritually inspiring courses were (1) intellectually enlightening and (2) applied religion to life. In lower‐ranked spiritually inspiring courses the themes (1) class time was ineffective and (2) poor assessments were prevalent. We explore the practical implications from these and other findings.